HOTAIR, a ferroptosis-related gene, promotes malignant behavior of breast cancer via sponging miR-206 - Wei Wu; Zhihan Yao; Yongxing Chen; Rongxuan Xu; Chenxin Jin; Xiaofeng Li (Discover Oncology)
Abstract Ferroptosis, an iron-dependent regulated cell death modality driven by lipid peroxidation cascades, has emerged as a critical pathogenic mechanism in tumorigenesis and therapeutic resistance. The long non-coding RNA HOTAIR (HOX transcript antisense RNA), previously recognized as a key epigenetic modulator in tumor biology, orchestrates malignant phenotypes through regulation of cell cycle dynamics, proliferative signaling, and metastatic potential. Despite these advances, the mechanistic interface between HOTAIR-mediated ceRNA networks and ferroptosis regulation in breast carcinogenesis remains undefined. Bioinformatic analysis and RT-qPCR validation precisely mapped the subcellular localization and interaction networks of this regulatory axis. Key findings revealed that HOTAIR silencing functionally promotes malignant phenotypes (proliferation, migration and invasion), and mechanistically serves as a molecular sponge for miR-206, thereby de-repressing CERS2 expression to modulate ferroptosis susceptibility. Given the established correlation between HOTAIR silencing and ferroptosis in BRCA, our data suggest that pharmacological induction of ferroptosis represents a promising therapeutic paradigm for this molecular subset. This work not only deciphers a novel HOTAIR/miR-206/CERS2 axis in ferroptosis regulation but also provides translational insights for developing biomarker-driven treatment strategies in refractory breast malignancies.